Abuse of Competitive Fringe - Carlo Capuano (Fondazione Eni Enrico Mattei (FEEM), 2005)
The purpose of this article is to analyze how the presence of a competitive fringe, composed by price taker firms, can affect the sustainability of collusive equilibria. Our starting point is that there exists a diffused misunderstanding about its strategical role as collusive minus factor. We deny that. In fact, if it is true that in single dominance cases the presence of a competitive fringe significantly reduces the price increasing profitability and the leader market power, when we consider collective dominance cases the deviation profitability and the punishment mechanism become crucial. In this paper after introducing a minimal structural and strategical framework needed for describing this kind of competition, we prove that not only the presence of a competitive fringe is a collusive plus factor, but also that there exists a critical dimension of the fringe such that collusion is a Nash equilibrium of the static game.
Keywords: D43; L1; L13; 330; Collusion; Oligopoly; Competitive fringe; Bertrand; Nash; Wettbewerbsbeschränkung; Oligopol; Nash-Gleichgewicht; Preiswettbewerb; Theorie